Long-Shaft Vitrectomy Probe for Vitreoretinal Diseases in Highly Myopic Eyes: A Randomized Controlled Trial - Yun Hsia, MD, MS; Cheng-Yung Lee, MD; Mei-Chi Tsui, MD; Shih-Wen Wang, MD; Chien-Jung Huang, MD; I-Hsin Ma, MD, MS; Kuo-Chi Hung, MD; Muh-Shy Chen, MD, PhD; Zih-Wei Yang, MD; Bo-Da Huang, MD; Ting-Chieh Ko, MD; Tzyy-Chang Ho, MD (Ophthalmology Science, 2025)
Objective: To evaluate the safety and efficacy of a long-shaft vitrectomy probe in highly myopic eyes undergoing pars plana vitrectomy. Design: A randomized controlled trial. Subjects: Highly myopic eyes (axial length [AL] >26 mm) with epiretinal membrane (ERM), myopic tractional maculopathy, and retinal detachment. Methods: The enrolled eyes were randomly assigned to a study group (UltraVit 25 Ga, 31.75 mm, Alcon) and a control group (UltraVit 25 Ga+, 27 mm, Alcon). Stratified randomization was performed to balance the proportion of eyes with AL >28 mm between groups. Main Outcome Measures: Trocar removal rate and core vitrectomy time were assessed as primary outcomes, and instrument bending as a secondary outcome. Anatomical and visual outcomes and complications were documented for 6 months. Subgroup analysis was performed to compare the eyes with AL >28 mm to those without. Results: We included 86 patients with a mean age of 60.7 ± 9.6 years and an AL of 29.15 ± 2.14 mm. Two groups had comparable core vitrectomy times (−0.5 minutes, P = 0.172). The study group had a lower trocar removal rate (5% vs. 67%, P < 0.001) but a higher instrument bending rate (36% vs. 14%, P = 0.036), particularly in eyes with AL >28 mm. In eyes with AL >28 mm, the standard vitrectomy probe faced a significantly greater difficulty in cortical vitreous removal, internal limiting membrane (ILM) trimming, or posterior vitreous detachment induction compared with the long-shaft vitrectomy (P < 0.001). At 6 months, significant visual improvement (logarithm of the minimum angle of resolution) and anatomical success were achieved (study: −0.22, 95%; control: −0.24, 88%). Eyes with ERM in the study group, not the controls, had significant visual improvement (−0.21, P = 0.02 vs. −0.09, P = 0.34). Conclusions: The long-shaft vitrectomy probe is safe and efficient, especially in highly myopic eyes with AL >28 mm, despite a higher instrument bending rate. It provides improved access to the posterior pole, allowing for delicate removal of adherent cortical vitreous and trimming of ILM flaps. Addressing increased instrument bending due to the sleeveless design is important for future design. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.